Cellular and molecular exercise physiology: A historical perspective for the discovery of mechanisms contributing to skeletal muscle adaptation - Sharples, A. P. (Cellular and Molecular Exercise Physiology, 2017)
Cellular and molecular exercise physiology is the study of the underlying regulatory mechanisms that underpin physiological adaptation to exercise. In this historical perspective, I explained how the field emerged following advancements in technology within the molecular biology field in general and as a result of some exciting forward thinking by the leading exercise biochemists of the time. I also discuss the important advancements in elucidating the mechanisms underlying physiological adaptation to exercise using genetic knockout, overexpression and compensatory hypertrophy models in animals that subsequently enabled the study and translation of key mechanisms that underpin human exercise adaptation. This historical perspective also helps decipher the important studies that pioneered the investigation of the cellular signaling networks controlling gene expression in response to acute and chronic exercise, the role of satellite cells in repair of skeletal muscle after exercise and finally how the important topic of exercise genetics/genomics emerged within the cellular and molecular exercise physiology field. Finally, the manuscript identifies that the integration of epigenetics and proteomics to compliment current genome-wide approaches (profiling of heritable genetic variants and gene expression) are likely to play an important role in uncovering the cellular and molecular regulation of exercise adaptation into the next generation.